THE HUSBAND’S OBLIGATION IN PROVIDING NAFAQAH TO THE WIFE DURING THE PANDEMIC HARDSHIP: AN ANALYSIS FROM AN ISLAMIC PERSPECTIVE - Jamal Abd. Nasir, Fatin Nasihah; Mat Jubri@Shamsuddin, Mustafa (Jurnal Syariah, 2024)
In mid-2020, the International Monetary Fund reported the effects of Covid-19 pandemic to have significantly contributed to severe financial difficulties, leading to delays in husbands providing financial support (nafaqah) to their wives. Financial challenges have emerged as the second most significant issue following health concerns during the COVID-19 pandemic, causing the husbands to face obstacles in meeting their obligation to support their wives financially. Consequently, to resolve this confusion, this paper aims to investigate the husband’s role as a custodian of rights in delivering financial support to his wife amid the pandemic from the Islamic perspective. Furthermore, it seeks to address inquiries and apprehensions regarding husbands who do not fulfil this responsibility, while also examining the concept of spousal maintenance from an Islamic viewpoint. This research is qualitative in nature. The method used in this study is library research, gathering information from both primary and secondary sources. The data will be organised using a thematic approach. The study found that the husband’s obligation to provide maintenance does not cease even during a pandemic; instead, it becomes a debt owed to the wife. However, the wife has the option to either remain in the marriage or seek a divorce. This finding clarifies misunderstandings and confusions within the community about the status of maintenance, aids husbands in understanding their responsibilities, demonstrates Islam’s flexibility in addressing the maintenance issues and encourages wives to exercise patience during difficult times, as this is one of the strengths of marriage.